Child behaviour problems mediate the association between coping and perceived stress in caregivers of children with autism. (December 2015) - Lovell, Brian; Wetherell, Mark A.
Highlights: Caregivers' perceived stress predicted by coping and child behaviour problems (CBP). CBP mediate the effect of disengaged coping on perceived stress scores. CBP mediate the effect of problem focused coping on perceived stress scores. Abstract: Coping and child behaviour problems (CBP) predict psychological distress in caregivers of children with autism. Whether CBP mediate the relationship between coping and caregivers' psychological functioning has yet to be determined. This was the aim of the current study. A sample of 56 caregivers of children with autism completed an electronic survey assessing perceived stress, disengaged and problem focused coping, and CBP. Disengaged and problem focused coping predicted both CBP and perceived stress, albeit in different directions. CBP was also predictive of perceived stress. Data revealed an indirect effect of both disengaged and problem focused coping on perceived stress through CBP. In conclusion, caregivers who use more disengaged coping might be less effective at managing the problematic behaviours of the child with autism, thus resulting in poorer psychological functioning. Conversely, caregivers who use more problem focused strategies might, due to fewer CBP, be relatively protected against the psychological sequelae associated with the caregiving experience. Whether interventions that enhance problem focused coping have adaptive effects for caregivers' psychological functioning, and whether these effects are mediated by fewer CBP might be the focus of subsequent research.